Educação física, educação ambiental e educação infantil no contexto escolar : uma sinergia possível - Rodrigues, Cae (Universidade Federal de São Carlos, 2007)
The pursuit for synergies between physical education and environmental education in elementary education stems from two main characteristics of contemporary life, namely the environmental crisis on the one hand, and the valorization of body culture, human movement, and ludic experiences in children development, on the other hand. The contemporary environmental crisis is substantiated by a disintegrated relationship between society and nature, precipitated by a fragmented awareness of the world that privileges human values and desires over nature. Once ensuing from this simplistic world view, that disregards a wealth of potential learning relationships, conventional environmental education has usually been uncritical and conservative. In order to meet a relentless human quest for a more meaningful societal life, for being-ones-with-the-others , for being more , a new education must be sought, one that comes to contend the bases of conservatism, a challenging education, set on liberty and aimed at intervening to change. To consider an environmental education that underscores the principles of a democratic education presupposes working with contents that are significant to the student, stressing the relevance of experience, of attitudes and values - all genuine marks of Freire s pedagogy. In elementary education, focus of this study, significant apprenticeship is proposed to be based on essential elements present in children s universe, such as movement, ludic experiences and the development of body culture. All these elements are present in the contents and pedagogic objectives of physical education. Hence, it is possible to define as objectives of this study: (i) to ascertain and ascribe the effective role of physical education in elementary education, (ii) seeking to promote children s environmental awareness. This research, which applies a typically qualitative approach, was carried out on the basis of a critical bibliographical review on the philosophical, pedagogical and methodological knowledge about the synergies between physical education and environmental education, emphasizing the potentialities of their relationships as concepts for understanding and proposing improved approaches regarding the building up of environmental awareness in childhood.
Keywords: Educação física; Educação ambiental; Educação de crianças; Concepção freiriana; CIENCIAS HUMANAS::EDUCACAO